تقويم جودة تطبيقات الويب باستخدام الاختبار المعتمد على النّماذج - يوسف دلا; سالي جركس (Tishreen University, 2018)
Software shifts more and more to the online world. Testing web applications is important to decrease cost and get high quality applications. Testing web applications requires documents that specify what their correct behavior is, and this makes testing difficult. In this study, we will test web application based on a model-based testing approach. We use Model Based Testing (MBT) for detection failures in web applications, and to apply functional testing so we overcome the drawbacks of traditional testing approaches, then we compare MBT with automatic testing according to time, number of errors and coverage criteria. We have chosen for the model-based testing approach because it automates the testing process, adapts quickly to changes, it is time saving, and less error prone if the system is modelled correctly. تُركِّز معظم الشّركات البرمجية توجهاتها على نشر منتجاتها باستخدام تطبيقات الويب، ولهذا فإن عملية تحديد الأخطاء مهمة جداً لتقليل التّكلفة والحصول على تطبيقات بجودة عالية. تتطلب عملية اختبار تطبيقات الويب تحديد السلوك الصحيح من خلال التوصيفات التي غالباً ما تكون غير موجودة. وهذا ما يشكل عائقاً في تحديد الأخطاء الممكن ظهورها في التطبيقات. سيتمّ في هذا البحث استخدام الاختبار المعتمد على النماذج Model based testing (MBT) لتحديد الأخطاء التي تحدث في تطبيقات الويب ولإجراء الاختبارات الوظيفية على النظام، وهذا يؤدي إلى تجاوز المشاكل التي تحصل في اختبارات تطبيقات الويب، ثم سيتم مقارنة أداء هذه الطريقة مع طريقة الاختبار الآلي وفقا لمعايير الزمن وعدد الأخطاء المكتشفة. تكمُن فعالية الاختبار المعتمد على النماذج في تطبيقات الويب بسهولة استخدامه للعمل الآلي والتكيُّف مع التغيرات السريعة إضافة إلى تخفيض الكلفة الزمنية والكشف المبكر عن الأخطاء في حالة النمذجة الصحيحة للتطبيق.